Neoplasia detection in FIT positive screening colonoscopies compared with an age-controlled symptomatic cohort: a retrospective review - O’Morain, Neil; Stack, Roisin; Doherty, Jayne; Nolan, Blathnaid; Girod, Parker; Kumar, Lakshman; McCrossan, Mark; Joy, Elaine; Casey, Orlaith; Horgan, Gareth; Doherty, Glen (Frontiers in Gastroenterology, 2024)
Colonoscopy following a positive FIT test in an average risk population is effective in reducing CRC incidence and mortality. While lower gastrointestinal symptoms remain a common cause for referral for colonoscopy, symptoms are poor predictors of clinically significant disease. The study was performed to compare neoplasia detection FIT +ve individuals and age-matched symptomatic cohorts. A single centre retrospective observational study was performed including all index colonoscopies performed on patients aged 60-70 from January 2015 to September 2021. Diagnostic yield was reported as adenoma detection rate, SSL detection rate, detection of high risk finding or adenocarcinoma. 8,106 colonoscopies were performed on patients aged 60-70 years. 3,695 (45.6%) originated from screening (FIT +ve). With exclusion criteria applied, 2,640 (59.9%) for screening and 1,767 (40.1%) for symptomatic patients were included. Median age in screening was 65 years (IQR 62-67) and 64 years in the symptomatic group (IQR 62-68), with male predominance in both groups (n=1,536, 58.1%, n=944, 53.4%). There were significant differences in both the ADR (56% vs 26.3%, p<0.01) and the SSLDR (10.4% vs. 8.1%, p=0.05) in the screening cohort compared to the symptomatic group. High risk findings (21.3% vs. 7.5%, p<0.01) were significantly more prevalent in the screening group with a considerably higher colorectal cancer (4.7% vs. 0.9%, p=<0.001) detection rate. FIT based triage significantly outperforms symptom based investigation for individuals in the 60-70 age group. Patients should be preferentially referred to organised colorectal cancer screening. FIT can be performed on symptomatic patients, to identify low risk individuals.